Effect of a Modest Weight Loss in Normalizing Blood Pressure in Obese Subjects on Antihypertensive Drugs - Luisa Gilardini; Gabriella Redaelli; Marina Croci; Antonio Conti; Lucia Pasqualinotto; Cecilia Invitti (Obesity Facts, 2016)
Objective: To assess the effect of a lifestyle intervention in lowering/normalizing blood pressure (BP) levels in hypertensive (controlled or not) obese patients. Methods: In this prospective observational study, 490 obese hypertensive patients, 389 controlled (BP Results: 18.9% of CH and 20.0% of UH were on ≥ 3 antihypertensive drugs. Weight change (average -4.9 ± 2.7%) was independent of the antihypertensive drugs employed. Systolic BP (SBP) decreased by 23 mm Hg and diastolic BP (DBP) by 9 mm Hg, in patients with UH most of whom (89%) normalized BP levels (in 49% after a weight loss Conclusion: Lifestyle interventions are useful for all obese hypertensive patients in most of whom a modest weight loss is sufficient to normalize BP levels avoiding the aggressive use of multiple antihypertensive drugs.